Learning System in Salaf and Khalaf Islamic Boarding Schools (Multiple Case Study in Lirboyo Islamic Boarding School, Kediri and Tebuireng Islamic Boarding School, Jombang) - Muhlisin; Irfan Fauzan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the learning system in the Salaf and Khalaf Islamic Boarding Schools (Multi Case Study at the Lirboyo Islamic Boarding School in Kediri and the Tebuireng Islamic Boarding School in Jombang). The learning methods of the Lirboyo Islamic Boarding School are sorogan, bandongan, memorization, deliberation, and bahsul masail. While the learning methods of the Tebuireng Islamic Boarding School are sorogan, bandongan, bahsul masail, lalaran, and muhadatsah. The learning curriculum of the Lirboyo Islamic Boarding School uses an independent curriculum that is based on discussions of topics in the yellow book that is used as a teaching resource. The Lirboyo Islamic Boarding School does not use a curriculum compiled by the Ministry of Religion that is based on specified topics without including references as a teaching resource. While the learning curriculum of the Tebuireng Islamic Boarding School uses an independent curriculum that is based on discussions of topics in the yellow book and also uses a curriculum compiled by the Ministry of Religion. The learning curriculum is delegated to existing educational units.